The Effect of Pro- and Eukaryotic Inductors on the Synthesis and Antimicrobial Activity of Acinetobacter calcoaceticus IMV B-7241 Surfactants - Pirog, T.P.; Ivanov, M.S.; Shevchuk, T.A.; Blagodyr, D.O.; Пирог, Т.П.; Іванов, М.С.; Шевчук, Т.А.; Благодир, Д.О. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
By now, the mixed cultivation ("co-cultivation") of antimicrobial compound producers with other microorganisms or the introduction of biological inductors in different physiological states (live and inactivated cells, as well as the corresponding supernatants) into the culture medium is a simple, cheap, and effective way to increase the synthesis of practically important microbial metabolites and regulate their biological activity. In most studies, researchers use bacterial strains of various species as inductors, however, in recent years, there have been an increasing number of publications reporting the use of eukaryotic inductors, in response to which there's observed an increase in the synthesis of antimicrobial compounds by the bacterial producers. In addition, the effectiveness of biological inductors depends on the conditions of their cultivation and physiological state. Aim. To study the effect of the methods of preparation and physiological state of biological inductors (gram-negative bacteria Enterobacter cloacae C-8 and yeast Saccharomyces cerevisiae BTM-1) on the activity of biosynthetic enzymes and antimicrobial activity of Acinetobacter calcoaceticus IMV B-7241 surfactants. Methods. Purified glycerol and crude glycerol in equimolar carbon concentration were used as a substrate for cultivation of A. calcoaceticus IMV B-7241. The microbial inductors were grown on both agar and liquid media with glucose as a carbon source. Live or inactivated cells of S. cerevisiae BTM-1 or E. cloacae C-8, as well as the corresponding supernatant, were added to the medium in an amount of 2.5–10 % (v/v). The extracellular surfactants were obtained from the supernatant of the culture liquid by extraction with a mixture of chloroform and methanol (2:1). The antimicrobial activity of surfactants against bacterial (Bacillus subtilis BT-2, Escherichia coli IEM-1, Staphylococcus aureus BMS-1, Pseudomonas sp. MI-2) and yeast (Candida albicans D-6 and Candida tropicalis PE-2) test cultures was determined by the indicator of the minimum inhibitory concentration. The activity of enzymes for the biosynthesis of surface-active glyco- (phosphoenolpyruvate carboxylase, phosphoenolpyruvate synthetase, phosphoenolpyruvate carboxykinase, trehalose phosphate synthase) and aminolipids (NADP+-dependent glutamate dehydrogenase) was analyzed in cell-free extracts obtained after sonication of cells. Results. The introduction into the culture medium of A. calcoaceticus of IMV B-7241 with glycerol of various purification degrees, both pro- and eukaryotic inductors in different physiological states was accompanied by the synthesis of surfactants, the antimicrobial activity of which against the test cultures was higher by one to two orders of magnitude compared to preparations obtained without inductors. It was found that E. cloacae C-8 cells grown in liquid medium were slightly more effective as inductors than those grown in agar medium: the minimum inhibitory concentrations against bacterial and yeast cultures of surfactants synthesised in their presence were 1–6 and 2.5–8 μg/mL, respectively. When live S. cerevisiae BTM-1 or E. cloacae C-8 cells were used as inductors, the production of microbial surfactants with higher antimicrobial activity than those synthesized in the presence of inactivated cells or supernatants was observed: the minimum inhibitory concentrations against the test cultures were in the range of 0.85–16, 2–20 and 1.5–22 μg/mL, respectively. The higher antimicrobial activity of surfactants synthesized in the presence of a pro- or eukaryotic inductor in the medium with purified glycerol may be caused by an increase of aminolipids in their composition, as evidenced by a 1.6–2.1-fold increase in NADP+-dependent glutamate dehydrogenase activity in A. calcoaceticus IMV B-7241 cells compared to the values of cultivation without inductors. The same level of activity of this enzyme during the cultivation of the IMV B-7241 strain in the medium with crude glycerol in the presence of inductors and without them may indicate the synthesis under such conditions of other, than aminolipids, metabolites with antimicrobial activity. Conclusions. As a result of this study, it was established that the antimicrobial activity of A. calcoaceticus IMV B-7241 surfactants can be increased by introducing pro- and eukaryotic inductors in the form of live or inactivated cells, as well as the corresponding supernatants into the medium with glycerol of different degrees of purification.